Thermal stability of amorphous nimesulide: from glass formation to crystal growth and thermal degradation - Svoboda, Roman; Macháčková, Jana; Nevyhoštěná, Marie; Komersová, Alena (Royal Society of Chemistry, 2024)
Thermally induced physico-chemical transformations in amorphous nimesulide were studied by means of differential scanning calorimetry (DSC), thermogravimetry, and Raman microscopy. The equilibrium glass transition temperature was found to be Tg0 = 10-15 degrees C, and the relaxation motions were found to be temperature-dependent. Crystal growth from the amorphous phase was found to be crucially dependent on the presence of mechanical defects that serve as centers for heterogeneous nucleation. The large amounts of mechanical defects significantly decrease the activation energy of the macroscopic crystallization; the positions of the crystallization peaks and their asymmetry/shape remain however almost unchanged. At laboratory temperature, powdered nimesulide fully crystallizes within several hours, with an absolute majority of the crystalline phase being formed as the thermodynamically stable form I polymorph. Amorphous nimesulide does not crystallize from the free smooth surface (no trace of formed crystallites was found by optical microscopy after 30 days at laboratory temperature). Nimesulide was found to be very stable at temperatures above its melting point of 147.5 degrees C; thermal degradation starts to proceed slowly at 200 degrees C. Mutual correlations between the macroscopic and microscopic crystal growth processes and between the viscous flow and structural relaxation motions were discussed based on the values of the corresponding activation energies. A link between the cooperativity of structural domains, parameters of the Tool-Narayanaswamy-Moynihan relaxation model, and microscopic crystal growth was proposed. Thermally induced physico-chemical transformations in amorphous nimesulide were studied by means of differential scanning calorimetry (DSC), thermogravimetry, and Raman microscopy.
Termální stabilita amorfního nimesulidu: od tvorby skla po růst krystalů a tepelnou degradaci
Keywords: enthalpy relaxation; phase-change; dsc cycles; kinetics; microstructure; temperature; dependence; polymers; dynamics; Tepelná stabilita; amorfní nimesulid; sklo; růst krystalů; tepelná degradace